Pope Francis's Preferential Option for Migrants, Refugees, and Asylum Seekers - Tan, Jonathan Y. (International bulletin of mission research, 2019)
Pope Francis's consistent advocacy for the human dignity and rights of migrants in his official pronouncements and actions reveals a pope who not only cares deeply about the existential challenges that migrants face but also articulates solutions to address these challenges. He unequivocally expresses a preferential option for, and commitment to, accompanying migrants in empathy and solidarity. He addresses issues of poverty, economic marginalization, environmental degradation, and racial, political, and religious tensions that drive migration today. For him, migration is a missional issue that undergirds the church's mission to bring the Good News to everyone, migrants included.